The effect of soil on cork quality - Pestana, Miguel N.; Gomes, Alberto A. (Frontiers in Chemistry, 2014)
The present work aimed to contribute for a better knowledge regarding soil features as cork quality indicators for stoppers. Cork sampling was made in eight Cork oak stands (montados de sobreiro) located in different Plio-Plistocene sedimentary formations of Península de Setúbal and Carbonic shistes from paleozoic periods in Saw Grândola, both in southern Tagus River region The samples used to classify the cork as stopper for wine bottles were obtained in eight cork oak stands located in “Península de Setúbal”, south of the River Tagus, covering soils of different types of sandstones of the Plio-plistocene In each stand, we randomly chose five circular plots with 30 m radius. Five trees with same stripping conditions determined by the dendrometric features: HD (height stipping, PBH (perimeter at breaster height), and percentage canopy cover, trees vegetative condition (defoliation degree) stand features (density), and site conditions (soil type and orientation). In the center of each plot a pit was open to characterize the soil profile and to classify the soil of each plot sampling. Cork quality for stoppers was evaluated according to porosity, pores/per cm 2 and thickness. The soil was characterized according to morphological soil profile features (lithology, soil profound and soil horizons) and chemical soil surface horizon features (organic matter, pH, macro and micronutrients availability). Based on the variables studied and using the numerical taxonomy, we settled relationships between the cork quality and some soil features. The results indicate: (1) high correlation between the cork caliber and boron, caption exchange capacity, total nitrogen, exchange acidity and exchangeable magnesium, potassium, calcium and sodium in soils of theirs cork oaks; (2) the cork porosity is correlated with the number of pores/cm2 and magnesium; (3) the other soil features have a lower correlation with the caliber, porosity and the number of pores per cm2.